2000
DOI: 10.1063/1.125833
|View full text |Cite
|
Sign up to set email alerts
|

Spin-tunnel-junction thermal stability and interface interdiffusion above 300 °C

Abstract: Spin tunnel junctions (CoFe/Al2O3/CoFe/MnIr) were fabricated with tunneling magnetoresistance (TMR) of 39%–41% after anneal at 300 °C, decreasing to 4%–6% after anneal at 410 °C. Junction resistance decreases from (0.8–1.6) to (0.5–0.8) M Ω μm2 during anneal. The pinned-layer moment decreases by 44% after anneal at 435 °C, but the free-layer moment does not change. The current–voltage characteristics change significantly and become asymmetric above 300 °C. Rutherford backscattering analysis (RBS) shows that ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(60 citation statements)
references
References 7 publications
2
58
0
Order By: Relevance
“…3, the spin polarization starts to degrade severely above 250°C, reminiscent of the degradation of TMR. 23 The degradation can be explained by contamination of the barrier/ ferromagnet interface by foreign atoms, [7][8][9] or by local oxidation of the ferromagnet as considered by Monsma and Parkin, 19 and earlier in this article. This direct comparison between the high-vacuum and the Ar-atmosphere anneal confirms that the polarization is vulnerable to diffusion of impurities.…”
Section: 12mentioning
confidence: 99%
“…3, the spin polarization starts to degrade severely above 250°C, reminiscent of the degradation of TMR. 23 The degradation can be explained by contamination of the barrier/ ferromagnet interface by foreign atoms, [7][8][9] or by local oxidation of the ferromagnet as considered by Monsma and Parkin, 19 and earlier in this article. This direct comparison between the high-vacuum and the Ar-atmosphere anneal confirms that the polarization is vulnerable to diffusion of impurities.…”
Section: 12mentioning
confidence: 99%
“…A similar Mn-diffusion-related deterioration of the MR has been measured on magnetic tunnel junctions with a CoFe/ IrMn top electrode. 16,17 While the thermal deterioration of the magnetotransport properties dominates any possible magnetic-field effects for the TSV structure, the exchange bias of the BSV structure clearly depends on the annealing field strength. The exchange bias field initially increases rapidly from 23 mT in the as-deposited state to 36 mT after annealing in a field of 0.5 T and this is followed by a more gradual increase to 39 mT for annealing in a field of 5.5 T. The influence of the annealing field strength can be understood by considering the microscopic origin of exchange bias in IrMn/ ferromagnetic bilayers.…”
Section: -3mentioning
confidence: 99%
“…Figure 3 For EB-SV MTJs having an AF layer containing Mn atoms, several mechanisms have been suggested for the drop in TMR ratios at high T a . These include, Mn diffusion from the AF into the ferromagnetic (F) layer and towards the barrier 11,12 , small exchange bias field (H ex ) 9 , and crystallization to face-centered cubic (fcc) structure/ (110) oriented body centered cubic (bcc) in the ferromagnetic layers. 9,14 We first consider the effect of H ex , which is plotted as a function of T a in Fig.…”
Section: (C)mentioning
confidence: 99%
“…We found that TMR ratios started to decrease when annealing temperatures (T a ) exceeded 425 o C. 8,9 Several mechanisms were suggested in the past as to the reasons for the decreased TMR ratios at high T a ; among these, Mn diffusion from the AF layer into the ferromagnetic layer and towards the barrier insulator is the most suspected in Al-O barrier MTJs. 11,12 In this letter, we fabricated pseudo SV (P-SV) MTJs that do not have Mn-based AF and SyF pinned layers with (100) oriented CoFeB/MgO/CoFeB by sputtering and annealed them at 250 -475 o C. We then compared the resultant TMR ratios with those of EB-SV MTJs with AF (MnIr) and SyF pinned layers. In the following, we mainly Fig.…”
mentioning
confidence: 99%